1988
DOI: 10.2307/1941164
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis of the Role of Emigration in Population Regulation of Desert Pupfish

Abstract: Pupfishes (genus Cyprinodon) have existed for long periods in small desert springs and streams that often lack competitors, major predators, and large environmental changes. How their populations are regulated in these systems is poorly known. We experimentally examined the role of emigration in regulating populations of pupfish by (1) comparing the dynamics of populations held in four pools open to emigration with those of populations held in four pools closed to emigration over a 22—mo period and (2) compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 54 publications
0
51
1
Order By: Relevance
“…In an experimental study assessing emigration of C. macularius, McMahon and Tash (1988) documented that small male fish were more likely to emigrate compared to large and/or female fish. In our study, however, we did not detect any differences in sex ratio or length of movers compared to non-movers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an experimental study assessing emigration of C. macularius, McMahon and Tash (1988) documented that small male fish were more likely to emigrate compared to large and/or female fish. In our study, however, we did not detect any differences in sex ratio or length of movers compared to non-movers.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, because limited resource availability often promotes emigration (McMahon and Tash 1988;McMahon and Matter 2006), we hypothesized that the upstream perennial regions are a source habitat that supplies individuals to downstream ephemeral sink habitats. Additionally, we hypothesized that movement rates will decrease throughout the course of the study, as pupfish establish breeding territories.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If social behaviour has an e ect on rates of emigration, then it must certainly have an e ect on self-thinning. In the case of territorial species like pup®sh (MacMahon & Tash 1988) or salmonids (Grant et al 1998), self-thinning may be strongly a ected by territorial behaviour. Unlike territorial salmonids or pup®sh, however, patterns of self-thinning we observed in cohorts of juvenile fathead minnows may have resulted, at least in part, from conspeci®c attraction.…”
Section: E F F E C T S O F E M I G R a T I O Nmentioning
confidence: 99%
“…The mechanism by which individuals are lost from a cohort or population, either via mortality or emigration, may have important e ects on population structure and dynamics (MacMahon & Tash 1988). The design of our experiments was similar to the study reported by MacMahon & Tash (1988 Finally, we were interested in contrasting patterns of self-thinning observed in a species with social behaviour that di ers dramatically from more commonly studied salmonid ®sh (Grant et al 1998). Unlike territorial salmonids, fathead minnows often exhibit strong conspeci®c attraction, such as schooling behaviour in response to predation risk (Theodorakis 1989;Hager & Helfman 1991).…”
Section: Introductionmentioning
confidence: 99%